Producción musical del tema Almas Separadas de la banda Legendario - Lozano Herrera, Gustavo Adolfo (2018)
The project presented to continuation has as it appoint “Separate Souls” creation of the ex-Legendary ecuadorian “band”, a song that belongs to the musical gender *Heavy Metal. The subject rescues of the forget and begins to produce under the supervisión of the musical producer Gustavo Lozano with the collaboration of musicians invited, expecting obtain the best results; giving him a new approach turning it into the in a ballade, where the combination of acoustic and electrical guitars improve the emotional sense of the song. The process of technical and musical production, has been oriented with the end to satisfy the planned requirements by the producer, using technical suitable of production, attaining an affine sonority to the gender arriving to be of the like of listen them. “Separate souls” tries to become attached to the listened by big exponents of the gender, so much in the auditory part like visual. Turning into a song that can be heard by affine people or no to the gender, with a big acceptance between the same.